Soft tissue conditioning around teeth: A narrative review - Carlos Parra; Ioannis Kormas; Panagiotis Afouxenides; Deborah Foyle (Elsevier, 2024)
Mucogingival surgery encompasses any procedure designed to correct defects in the morphology, position, or enhance the dental gingival junction. The lack of keratinized gingiva and the presence of gingival recession can be an esthetic and functional problem for the patient. This paper will review the gingival dimensions of the periodontium in health and address the prevalence, etiology, and predisposing factors related to defects in the quality and quantity of gingiva.Gingival augmentation techniques and indications will be reviewed, including root coverage and non-root coverage procedures. Autogenous soft tissue grafts will be described, as well as several non-autogenous graft materials.Ultimately, careful diagnosis, realistic expectations, clear goals, and correct technique selection are essential for the most successful clinical results.